"DEVELOPMENT OF DESIGN AND CONSTRUCTIVE THINKING ON THE BASIS OF NATIONAL CRAFTS" (Universal International Scientific Journal, 2026)
This article covers the theoretical and methodological foundations and practical mechanisms of developing design and constructive thinking based on national crafts. The study analyzes the issues of integrating modern pedagogical approaches, a competency-based education model, digital transformation processes and artificial intelligence technologies into the educational process. Ceramics, embroidery, woodcarving and other types of national crafts are justified as effective didactic tools for developing design thinking, algorithmic and critical thinking. Also, the effectiveness of the project method based on an individual and inclusive approach, pedagogical monitoring and evaluation mechanisms are scientifically explained. The results of the study show that the integration of national heritage and modern innovations serves to develop the creative intellectual potential of students
Keywords: national crafts; design thinking; constructive thinking